STRATEGI MENCIPTAKAN BUDAYA RELIGIUS DI SEKOLAH - Supriyanto, Supriyanto (Jurnal Tawadhu, 2018)
In today's global era, the main issue we face is how to prepare human and religious human resources that are able to compete and not get lost in facing the life of the culture of science and technology. The atmosphere of modern life with massive culture and fulfilled various mobility of life technologically-mechanically, on the one hand has given rise to an ethical and moral crisis. The above phenomenon can not be separated from the lack of correct understanding of religion and religiosity (religiosity). For a success in the world of education, the solution in overcoming the less successful educational world in the problem one of them using approach of application of religious culture.Religious culture is an abstract idea or human thought and then applied or manifested through behavior or human behavior based on religious values. Strategy to realize religious culture requires teachers to be creative in realizing the religious culture in school, so that makes the citizens of schools, especially students can behave religiously according to their religious values.